O‘SIMLIKLAR HIMOYASIDA RAQAMLASHTIRISH TEXNOLOGIYALARI VA ULARNI YECHISHGA MO‘LJALLANGAN MOBIL ILOVALAR - Yaxyaev Xashim Kasimovich, Abdullaeva Xuriyatxon Zafarbekovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
It also provides descriptions and examples of the application of the developed mobile applications for smartphones such as ANDROID in agricultural production, including in the field of plant protection. The scientific and organizational tasks of their application are outlined, descriptions of the use of six developed mobile applications for phones of the ANDROID type are given, which contribute to the identification of types of harmful organisms in agricultural crops and the organization of protective measures.